Effect of mechanical factors on tribological properties of palm oil methyl blended lubricant - Maleque, Md. Abdul (Elsevier, 2000)
The effects of mechanical factors viz. applied load and temperature on the tribological performance of 5% palm oil methyl ester POME. blended lubricant were studied using a steel–cast iron pair. Wear and frictional measurements were made using a stationary steel ball and a reciprocating cast iron plate in a modified universal wear and friction testing machine. The test conditions were contact pressure, 400 MPa; mean contact velocity, 0.34 mrs; reciprocating stroke, 80 mm; loads, 100–1100 N fixed temperature.; and temperature, 40–1408C fixed load.. Wear scar surfaces were investigated using scanning electron microscopy SEM. to understand the wear mechanisms involved. Analysis of post bench test lubricating oils was performed using an ISL viscometer and TANrTBN analyzers to investigate the lubricating oil degradation properties. Results showed that at lower loads up to 500 N. and temperatures up to 1008C., the wear rates under 5% POME lubricant are lower, whereas at higher loads and temperatures, the wear rates are higher. The friction behavior of POME as an additive in commercial lubricant indicates the prevalence of the boundary lubrication regime. The viscosity test results showed that 5% POME can improve the viscosity index VI. properties of mineral-based lubricant up to 500 N load. However, in this investigation, corrosive wear and pits on the damaged surface are the dominant wear mode at higher temperature.